Microstructure Transformations in a Press Hardening Steel during Tailored Thermomechanical Processing. Issue 1 (16th September 2021) - Westermann, Hendrik; Reitz, Alexander; Mahnken, Rolf; Schaper, Mirko; Grydin, Olexandr
Abstract : Microstructure transformation due to thermomechanical processing has an acute effect the macroscopic properties of low‐carbon steels. This effect includes viscoplastic deformation and phase transformations. Hot forming processes such as press hardening are particularly affected. Most engineering applications require a combination of high strength and sufficient residual ductility, which can be achieved by the development of graded microstructures. Herein, the evolution of phase transformations is investigated by linking experiments and simulations to produce graded microstructures. For this purpose, an extended material model is proposed to represent the evolution of phase transformations under inhomogeneous heating and cooling strategies. On the experimental side, phase transformations are identified during thermomechanical treatment of flat steel specimens using digital image correlation and thermal imaging. Based on the experimental results, the material parameters are identified, and the simulation model is validated. On the numerical side an algorithm for the finite‐element simulation of phase transformations in low‐carbon steels is proposed. The evolution of phase transformations is presented for the simulation of a tensile specimen using the finite‐element method. Abstract : The prime novelty of this research is a combination of new experimental and theoretical approaches to analyze microstructural transformations during tailored thermomechanical processing. The influence of differential thermal and strain conditions on the transformation kinetics is characterized using a novel contactless measuring method and a novel thermodynamic framework for the simulation of phase transformations is developed.